Evaluating the Factors Influencing Decision to Pay for Plastic Waste Treatment of Households in Cau Giay District, Hanoi City, Vietnam - Tien, Nguyen Dinh; Ngoc Thuy, Mai Diem; Ngoc Thuy, Mai Diem (VNU Journal of Science: Policy and Management Studies, 2024)
Plastic waste pollution is becoming more and more serious, posing a direct danger to human and animal health. Plastic waste treatment is an issue that receives much attention from many countries. With its bustling pace of life and economic development, Cau Giay District also faces a large amount of plastic waste generated daily without effective treatment measures. This paper used the Binary regression model to evaluate the willingness to pay and the main influencing factors on household's payment decisions. Factors such as media, gender, education, interest, and age all impact the payment decision making of local households. According to survey results, 79.8% of people agree to pay for the "plastic waste treatment fund", with a willingness to pay of about 133,570 VND per household.